Functional atlas of the human fascial system - Stecco, Carla; Hammer, Warren I.; ScienceDirect eBooks ([Edinburgh] : Churchill Livingstone, 2015)
Principally based on dissections of hundreds of un-embalmed human cadavers over the past decade, Functional Atlas of the Human Fascial System presents a new vision of the human fascial system using anatomical and histological photographs along with microscopic analysis and biomechanical evaluation. Prof. Carla Stecco - orthopaedic surgeon and professor of anatomy and sport activities - brings together the research of a multi-specialist team of researchers and clinicians consisting of anatomists, biomechanical engineers, physiotherapists, osteopaths and plastic surgeons. In this Atlas Prof.
Deep Fascia of the Neck: Superficial Lamina (Investing Layer or Layer I)Deep Fascia of the Neck: Middle Lamina (Layer II); Deep Fascia of the Neck: Deep Lamina (Prevertebral Fascia or Layer III); References; Bibliography; 5 Fasciae of the Thorax and Abdomen; Introduction; Superficial Fascia of the Thorax and Abdomen; Mammary Region; Deep Fascia; Pectoral Fascia; Clavipectoral Fascia; Intercostal and Endothoracic Fasciae; Deep Fasciae of the Abdomen; Fascia of the External Oblique Muscle; Fascia of the Internal Oblique Muscle; Fascia of the Transversus Abdominis Muscle; Rectus Sheath.
Print version record.
Includes bibliographical references and index.
Bibliography2 Subcutaneous Tissue and Superficial Fascia; History; Current Evidence; Superficial Adipose Tissue; Superficial Fascia (Fascia Superficialis) ; Deep Adipose Tissue; Transverse and Longitudinal Lines of Adhesions; Longitudinal Adhesions; Transverse Adhesions; Subcutaneous Vessels; Arteries; Veins; Lymphatic Vessels; Subcutaneous Nerves; Subcutaneous Bursa; Development of the Superficial Fascia; Mechanical Behaviour; Imaging of the Superficial Fascia; References; Bibliography; 3 Deep Fasciae; Introduction; Definition; Aponeurotic Fascia; Microscopic Anatomy of Aponeurotic Fasciae.
Elsevier
Keywords: Fasciae (Anatomy) -- Physiology -- Atlases; Connective tissues -- Physiology -- Atlases; MEDICAL -- Anatomy; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Fascia -- physiology; Connective Tissue -- physiology; Connective tissues -- Physiology; Electronic books